Dampak Pernikahan Dini pada Remaja Bagi Pendidikan Karakter Anak Dalam Keluarga di Muaro Paiti Kecamatan Kapur IX Kabupaten Lima Puluh Kota - Sonia Afrilia Sari; Muhiddinur Kamal; Linda Yarni; Alfi Rahmi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
In the background of early marriage is an underage marriage, in this case the preparation of a child or teenager is not fully maximised, both in mental, psychological, and even material preparation. When marrying at an early age, teenagers do not have enough knowledge about marriage, family and do not know how to manage conflict well, so that it will cause quarrels in the family and make the marriage less harmonious. Character education is the process of instilling character as well as providing seeds so that children are able to grow character, especially when running life, in other words, students not only understand education as a form of knowledge, but also make it a part of life and consciously live based on that value. This research is a descriptive qualitative field research. The key informants of this research are young women who married at an early age. The method of collecting data is through observation and interviews. Based on the results of the study, it shows that early marriage has an impact on adolescents such as economy, health, education, besides that early marriage also has an impact on children's character education such as a sense of responsibility, mutual respect, socialisation.